Econometric methods for causal evaluation of education policies and practices: a non-technical guide - Martin Schlotter; Guido Schwerdt; Ludger Woessmann (Institute for the Study of Labor (IZA), 2010)
Education policy-makers and practitioners want to know which policies and practices can best achieve their goals. But research that can inform evidence-based policy often requires complex methods to distinguish causation from accidental association. Avoiding econometric jargon and technical detail, this paper explains the main idea and intuition of leading empirical strategies devised to identify causal impacts and illustrates their use with real-world examples. It covers six evaluation methods: controlled experiments, lotteries of oversubscribed programs, instrumental variables, regression discontinuities, differences-in-differences, and panel-data techniques. Illustrating applications include evaluations of early-childhood interventions, voucher lotteries, funding programs for disadvantaged, and compulsory-school and tracking reforms.
Keywords: I20; C01; 330; Causal effects; education; policy evaluation; non-technical guide; Bildungspolitik; Wirkungsanalyse; Kausalanalyse; Ökonometrie